(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
Venezuela through a severe social, economic and political crisis, however, is a privileged, rich in natural resources, has an extensive infrastructure and professional talent that placed it among the countries with the highest rates of entrepreneurship early. In this context appear the idea of generating a polygon of innovation in Barquisimeto, a proposal for urban, social and economic renewal that seeks to become a sector of this city a centrality of working and mixed uses through innovation centers for training of entrepreneurs, single companies and areas of coworking, capable of attracting investors, national and international; linked with the universities of the region and proposing new recreational spaces, ways of living, mobility and living the city. Proposed innovation polygon is on 300 hectares, it will generate some 97,500 jobs, 458 accomodation for companies, 5,200 homes and 120 hectares of public space considering a new model of city that densify and diversify the use of the urban ground from technology and knowledge-intensive activities. For this purpose, is required the participation of the State, universities, private companies and the community; so it is proposed the creation of apromoter.